Dinamika Kekerasan Seksual yang Terjadi di Lingkungan Kampus: Tinjauan Terhadap Faktor Penyebab dan Upaya Untuk Menguranginya - Irsan Mawardi Sofyan; Novelin Ingrid Eka Sukma; Aisyah Nur Izzah; Thoriq Nashruddin Althof; Supriyono Supriyono (LPPM Politeknik Pratama, 2024)
In recent years, sexual violence on campus has become a serious issue that many people pay attention to. This research aims to analyze what factors cause sexual violence on campus and what efforts can reduce the number of sexual violence on campus. This data collection technique was carried out using questionnaires and interviews. Based on research results, the causes of sexual violence are caused by several factors, namely: social factors, environmental factors, clothing factors, and the power gap factor between the perpetrator and the victim. Apart from that, this observation also analyzes efforts that can reduce sexual violence that occurs on campus, such as increasing education about sexual violence, anti-sexual violence policies, and establishing institutions that handle cases of sexual violence. The research results show that, even though the steps have been taken, the problem of sexual violence in the campus environment still occurs frequently and is a very serious problem. In dealing with this, further action is needed in terms of education, support for victims, and enforcing effective policies regarding sexual violence.